Association of Serum Gamma-Glutamyl Transferase and Ferritin with the Metabolic Syndrome. (21st June 2015) - Wei, Dong; Chen, Tao; Li, Jie; Gao, Yun; Ren, Yan; Zhang, Xiangxun; Yu, Hongling; Tian, Haoming
Abstract : Aim . To investigate the relationship among GGT, ferritin, and the risk of metabolic syndrome. Methods . A total of 1024 eligible individuals of the Chinese Yi ethnic group were enrolled in this cross-sectional study. The presence of metabolic syndrome was determined using the revised NCEP-ATP III and CDS criteria. Odds ratios for the metabolic syndrome and its components for different groups based on the levels of GGT and ferritin were calculated using multiple logistic regressions. Results . Serum GGT and ferritin concentrations were significantly higher in subjects with metabolic syndrome compared to those without metabolic syndrome in both genders ( p < 0.05). Serum GGT was positively correlated with ferritin ( p < 0.05). The risk of the metabolic syndrome was significantly higher in female subjects who had elevated GGT and ferritin levels ( p < 0.05). Furthermore, the increased risk of having each of the metabolic syndrome components (overweight or obesity, hypertriglyceridemia, hypertension, hyperglycemia, and insulin resistance) was also observed in those subjects after adjustment for possible confounders ( p < 0.05). Conclusions . These data indicate that GGT and ferritin synergistically correlate with the risk of the metabolic syndrome, suggesting that they could potentially be used as predictive biomarkers for the metabolic syndrome.